2018
DOI: 10.1016/j.socec.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between status and happiness: Evidence from the caste system in rural India

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…In line with the authors' hypothesis, the results revealed significant caste differences, which align with previous studies that suggest lower-caste individuals have lower well-being and life satisfaction (Fontaine & Yamada, 2014;Landeghem & Vandeplas, 2018;Spears, 2016). However, as discussed beforehand, most previous studies focused on rural areas where caste plays a dominant role in everyday life.…”
Section: Caste Differencessupporting
confidence: 91%
See 1 more Smart Citation
“…In line with the authors' hypothesis, the results revealed significant caste differences, which align with previous studies that suggest lower-caste individuals have lower well-being and life satisfaction (Fontaine & Yamada, 2014;Landeghem & Vandeplas, 2018;Spears, 2016). However, as discussed beforehand, most previous studies focused on rural areas where caste plays a dominant role in everyday life.…”
Section: Caste Differencessupporting
confidence: 91%
“…Higher levels of depression have been found in individuals from lower castes (Mathias et al, 2015) and have the highest odds of hypertension compared to privileged upper caste members (Uddin et al, 2020). In terms of life satisfaction, the castes at the top are more satisfied than the lower and middle castes (Fontaine & Yamada, 2014;Landeghem & Vandeplas, 2018;Spears, 2016). In Nepal, a country that follows a caste system similar to India, youth from low caste groups reported more anxiety, depression, and low selfesteem than their counterparts from other caste groups (French, 2020;Kiang et al, 2020).…”
Section: Caste Gender and Well-beingmentioning
confidence: 99%
“…This indicates the existence of caste-based socioeconomic disparities in the Indian society. The upward trend in socioeconomic indicators across the hierarchy of caste demonstrates how higher social status brings advantages and opportunities in life [ 38 ]. As a result, people who belong to the upper castes are more satisfied than those from the lower castes, like the SC/ST group.…”
Section: Discussionmentioning
confidence: 99%
“…In 1972, King Jigme Singye Wangchuck IV of this Himalayan nation declared that 'Gross National Happiness (GNH) is more important than Gross National Product', a proclamation that defies prevalent economic development principles around the earth. The king's proclamation underlines that Bhutan's progress will grow out of its own cultural milieu (Ura, 2012). The original four pillars of GNH are sustainable and equitable development, environmental conservation, the preservation and conservation of culture and good governance.…”
Section: State-of-the-art Of Quality Of Life In the Regionmentioning
confidence: 99%
“…Numerous studies portray caste as a dominant factor impacting life in India (Deshpande, 2000; Bloch et al., 2004; Anderson, 2006; Carlsson et al., 2009; Banerjee et al., 2013). Van Landeghem and Vandeplas (2018) found that people higher in the caste ladder are better off in many ways. Nevertheless, people in the higher castes are more satisfied in life in various ways compared to the rest, and people in the middle caste are less happy than the lower castes.…”
Section: State‐of‐the‐art Of Quality Of Life In the Regionmentioning
confidence: 99%